2011
DOI: 10.1021/ie101439x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Crystalline-Phase Silica-Based Calcium Phosphonate Nanomaterials and Their Transport in Carbonate and Sandstone Porous Media

Abstract: Phosphonates are widely used scale inhibitors in oilfields for scale control. In this study, crystalline-phase calcium phosphonate nanomaterials were prepared from amorphous silica-templated calcium phosphonate precipitates that were matured into crystalline phases by a simple diafiltration process. The crystalline solids were further dispersed into a surfactant solution to form a nanomaterial suspension (nanofluid) by ultrasonic treatment to expand their use in the delivery of phosphonate inhibitors into form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 54 publications
0
39
0
Order By: Relevance
“…Incorporation of multiple transport mechanisms in continuum models and their application in complex, realistic domains and scales is not computationally efficient. The use of a partitioning (distribution) coefficient in NP transport modeling is desirable because it reduces the number of parameters in the attachment/detachment process from two ( and ) to one ( ), and more importantly facilitates the application of many analytical solutions and numerical tools for the governing equation [88,[354][355][356]. However, the use of nominally requires the assumption of an equilibrium state between the suspended and attached phases which has been recently debated in the context of NP fate and transport [12,88,112,114].…”
Section: Equilibrium Vs Kinetic Terms In Continuum Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of multiple transport mechanisms in continuum models and their application in complex, realistic domains and scales is not computationally efficient. The use of a partitioning (distribution) coefficient in NP transport modeling is desirable because it reduces the number of parameters in the attachment/detachment process from two ( and ) to one ( ), and more importantly facilitates the application of many analytical solutions and numerical tools for the governing equation [88,[354][355][356]. However, the use of nominally requires the assumption of an equilibrium state between the suspended and attached phases which has been recently debated in the context of NP fate and transport [12,88,112,114].…”
Section: Equilibrium Vs Kinetic Terms In Continuum Modelsmentioning
confidence: 99%
“…Conceptually the equilibrium assumption is invalid since is physically based on the Gibb's energy and thermodynamic equilibrium assumption, while NP suspensions are thermodynamically unstable [114]. On the other hand, several authors have successfully utilized the concept of in modeling NP transport, mostly in form of type (v) models (Tables 1 and 2) [146,147,180,182,190,355,357]. This is also in accordance with numerous experimental studies observing retarded BTCs [124, 138, ) onto soil and found out that the sorptivity of both of them followed the Freundlich isotherm with much stronger sorption obtained for CuO NP compared to Cu 2+ .…”
Section: Equilibrium Vs Kinetic Terms In Continuum Modelsmentioning
confidence: 99%
“…The advantage of such a material is that due to its low solubility, this material should be able to return DTPMP inhibitor at a much lower return concentration, which means that the squeeze lifetime will be greatly extended for a given amount of inhibitor squeezed into formation. The first reported synthesis study of crystalline Ca-DTPMP was conducted using silica nanomaterials as the template (Zhang et al, 2011b). The synthesis approach involves mixing of a DTPMP containing solution with another Casilica slurry solution to form a white precipitate of Ca-DTPMP.…”
Section: Metal-inhibitor-based Scale Inhibitor Nanomaterials Amorphoumentioning
confidence: 99%
“…Shen et al [40] prepared Ca-DTPMP nanosized particle suspensions (nanofluid) via chemical precipitation with the assistance of PPCA. In another study, Zhang et al [43] synthesized crystalline-phase Ca-DTPMP nanomaterials by converting the amorphous-phase solids using a dialysis filtration method to allow rapid dissolution of the amorphous inhibitor material. These authors also investigated the mobility and inhibitor return properties of the prepared nanomaterials in columns packed with calcite (Iceland spar) and Frio sandstone, respectively.…”
Section: Recently Developed Squeeze Treatment Techniquesmentioning
confidence: 99%